PENGARUH VARIASI SUDUT KAMPUH DAN KUAT ARUS PADA SAMBUNGAN BAJA KARBON MENENGAH TERHADAP KEKUATAN TARIK HASIL PENGELASAN SMAW - Suwarto; Suparno, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Welding is a process of joining two metals where the metals become one due to heat with or without pressure. In this research, the welding process was carried out using a SMAW (Shield Metal Arc Welding) welding machine or electric arc welding using E6013 wrapped electrodes to determine the effect of seam type and current on the mechanical properties of the weld results. The base metal used is medium carbon steel, namely AISI E 2512. The welding variables chosen are seam angles 600, 700, and 800, while the current variables used are 100A, 90A and 80A. Then tensile strength testing is carried out and the results of this research are The highest tensile strength is found at a seam angle of 800 and a current of 100A, namely 356.79 MPa, for the 700 seam angle group the highest tensile strength value is 339.05 MPa, while the lowest value is at a seam angle of 600 with a current of 80A of 296.97 MPa and properties. The weld mechanism will depend on the seam shape and current selected, so the seam angle and current strength have a significant influence on the tensile strength